2009
DOI: 10.1227/01.neu.0000330400.68015.88
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Clamp-Assisted Clipping of Thick-Walled Giant Aneurysms

Abstract: The DeBakey vascular clamp is helpful in assisting direct clipping of thick-walled giant aneurysms with a partially calcified atheromatic base. Some practical features of this instrument require further refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the past, large, heavy clips, at times supplemented by booster clips, were used in attempts to close atheromatous aneurysm necks. 2,20,22,26 Recently, Navratil et al 27 reported their experience with crushing the neck of these aneurysms using various hemostats. Although this maneuver may be successful in select cases, the technique can result in embolic complications, dissection or occlusion of the parent artery, and even rupture of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, large, heavy clips, at times supplemented by booster clips, were used in attempts to close atheromatous aneurysm necks. 2,20,22,26 Recently, Navratil et al 27 reported their experience with crushing the neck of these aneurysms using various hemostats. Although this maneuver may be successful in select cases, the technique can result in embolic complications, dissection or occlusion of the parent artery, and even rupture of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Wrapping of the aneurysm with cotton or other materials has been used as an alternative treatment for "unclippable" aneurysms, but this method is not considered durable. 7,13 The DeBakey vascular clamp-assisted clipping of giant aneurysms with a partially calcified atheromatic base has been described, 28 and this method can facilitate direct clipping in some rare cases. If previously performed coil embolization or stent placement has failed, clipping may be impossible with the endovascular material inside the vessel or aneurysm lumen.…”
Section: Treatment Principlesmentioning
confidence: 99%